Commuters' fear of crime and road transport industry: A case study of Ibadan-Sokoto Transport Corridor. (2009)
Human activities are conducted over space and this includes movement from one geo-location to another. This major need for movement is mostly serviced by the road transport industry made up of public and private investors. To protect consumers in this sector, various policies and regulations have been put in place not only to ensure value for money and standard but also for the safety and security of commuters and transport operators alike. This however seems like a mirage as criminal activities are steadily shifting from neighbourhoods and settlements to the highways. This paper is an effort towards understanding the situation of things in terms of validity of various reports and extent of such crimes along the Ibadan-Sokoto transport corridor, the state of fear amongst commuters, the effects of this on the road transport industry and stakeholders (transport owners, community and the commuters). The findings showed the apprehension of commuters along this highway and increasing criminal activities in specific points on the highways. Aside from measures taken by commuters and commercial drivers to 'beat' such criminals, communities along the corridor have established local guards to protect commuters who often pay tokens to maintain their services. It is concluded that there is need to re-address the country's highway policing strategy and thus look for ways to integrate and provide technical assistance to local vigilantes who are becoming increasingly relevant on long distance routes in Nigeria.